TEORI KONSUMSI DALAM EKONOMI ISLAM - Gustia Gustia; Nur Kholis; Sirajuddin Sirajuddin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
Islamic economics views consumption as being based on needs rather than desires, which differentiates it from conventional economics. Islam prohibits extravagance and equates it with satanic behavior. In Islam, consumption is focused on needs rather than wants to prevent wastefulness and encourage responsible behavior. Islamic teachings emphasize the moderate and responsible use of resources in consumption patterns. This study aims to determine how Islamic microeconomic literature describes consumption theory. This research is a qualitative literature review with a descriptive approach. The study collects data by analyzing journals, books, and other sources relevant to the research topic